2017
DOI: 10.1016/j.carbon.2017.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Tomography-based radiative characterisation of decomposing carbonaceous heat shield materials

Abstract: a b s t r a c tThis work evaluates the changes in radiative properties of two decomposing carbonaceous porous materials, each composed of two semi-transparent, homogeneous and isotropic phases. The understanding of the complex dependence of macroscopic optical behaviour on material microstructure, bulk phase properties and the wavelength of incoming radiation is paramount for modelling, design and optimisation of systems incorporating such media. Experimental and numerical techniques were combined to solve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…(2) - (6) are the general form of volume-averaged RTEs in heterogeneous two-component medium. Specifically, these equations take into account that the medium hosting the fibers and the fibers themselves may absorb and scatter radiation [41] . In that case, the radiation propagation in the phase i (air or fiber substance) can be described by intrinsic radiative properties namely intrinsic extinction β int, i , absorption κ i , and scattering coefficients σ i , and phase function i .…”
Section: Multi-rte Approachmentioning
confidence: 99%
“…(2) - (6) are the general form of volume-averaged RTEs in heterogeneous two-component medium. Specifically, these equations take into account that the medium hosting the fibers and the fibers themselves may absorb and scatter radiation [41] . In that case, the radiation propagation in the phase i (air or fiber substance) can be described by intrinsic radiative properties namely intrinsic extinction β int, i , absorption κ i , and scattering coefficients σ i , and phase function i .…”
Section: Multi-rte Approachmentioning
confidence: 99%
“…Cellular materials [1] such as open-cell foams, manufactured lattices, fibers felts exhibit interesting properties such as high strength-to-weight ratio, high surface-to-volume ratio, good flow-mixing capacity which make them suitable for several engineering applications. Certain high temperature applications where cellular porous materials are used include solar power power plants [2][3][4], heterogeneous combustion [5], thermal protection systems [6][7][8][9], etc. Note that, for porous samples having mean characteristic size of their constituents greater than a few microns or much greater than the size of thermal radiation can also be refereed as macroporous materials [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Advanced materials made of CF such as carbon-carbon composites, CF reinforced composites, and reinforced carbon-carbon are widely used as filtration membranes, 1 electrodes of fuel cells, 2,3 braking systems in aerospace and automotive industries, 4,5 and thermal protection systems. [6][7][8][9][10] With continuous advancement in material technology, the study of thermal properties of these materials has been an interesting topic for researchers and industrialists.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been devoted to correctly estimate the thermal properties (e.g., specific heat capacity, thermal diffusivity, and thermal conductivity) of above mentioned materials at different scales either through experimental 10,11 or numerical means. 6,7,10,12,13 Although the methods to estimate thermal properties at macroscopic scale have been discussed in numerous studies, very limited information for microscopic materials such as CF can be found. This is not only due to the microscopic size of the fibers which requires advanced tools but also due to the large variation of the thermal conductivity of these materials with temperature and their structural organization.…”
Section: Introductionmentioning
confidence: 99%